Variants in the FFAR1 gene are associated with beta cell function. - Martins Kalis (Public Library of Science (PLoS), 2007)
Background The FFAR1 receptor is expressed mainly in pancreatic beta cells and is activated by medium to long chain free fatty acids (FFAs), as well as by thiazolidinediones, resulting in elevated Ca(2+) concentrations and promotion of insulin secretion. These properties suggest that FFAR1 could be a mediator of lipotoxicity and a potential candidate gene for Type 2 diabetes (T2D). We therefore investigated whether variations at the FFAR1 locus are associated with T2D and beta cell function. Methodology/principal findings We re-sequenced the FFAR1 region in 96 subjects (48 healthy and 48 T2D individuals) and found 13 single nucleotide polymorphisms (SNPs) 8 of which were not previously described. Two SNPs located in the upstream region of the FFAR1 gene (rs1978013 and rs1978014) were chosen and genotyped in 1929 patients with T2D and 1405 healthy control subjects. We observed an association of rs1978013 and rs1978014 with insulinogenic index in males (p = 0.024) and females (p = 0.032), respectively. After Bonferroni corrections, no association with T2D was found in the case-control material, however a haplotype consisting of the T-G alleles conferred protection against T2D (p = 0.0010). Conclusions/significance Variation in the FFAR1 gene may contribute to impaired beta cell function in T2D.